Seagrass Enhalus acoroides extract mitigates obesity and diabetes via GLP-1, PPARγ, SREBP-1c modulation and gut microbiome restoration in diabetic zebrafish - Marcello Mikhael Kadharusman; Rony Abdi Syahputra; Rudy Kurniawan; Edwin Hadinata; Raymond Rubianto Tjandrawinata; Nurpudji Astuti Taslim; Raffaele Romano; Antonello Santini; Fahrul Nurkolis (Diabetology & Metabolic Syndrome)
Abstract Background The global rise in obesity and type 2 diabetes highlights the need for safe and effective therapeutic interventions. Enhalus acoroides is a tropical seagrass rich in carotenoids and other bioactives. Its potential for metabolic regulation has been suggested in vitro, but in vivo efficacy and molecular mechanisms remain unexplored. This study aimed to evaluate the anti-obesity and anti-diabetic effects of Enhalus acoroides extract (SEAE) in a zebrafish model of diet- and glucose-induced metabolic dysfunction. Methods Adult zebrafish were subjected to overfeeding and glucose immersion, after overfeeding and 14 days of glucose immersion to induce diabetes, adult zebrafish were randomized into three groups: untreated diabetic, SEAE-treated (5 mg/L), and metformin-treated (3.3 mg/L) for 20 days. Body weight, fasting blood glucose, lipid profile, gene expression (GLP-1, PPARγ, SREBP-1c), and gut microbiota profiles via 16 S rRNA sequencing were assessed. Results SEAE significantly reduced body weight and blood glucose in diabetic zebrafish (p < 0.05), with efficacy comparable to or exceeding Metformin. It upregulated GLP-1 and downregulated PPARγ and SREBP-1c. SEAE also reduced total cholesterol, triglycerides, and LDL levels, while increasing HDL levels. Moreover, SEAE restored the Firmicutes/Bacteroidetes ratio, increased alpha diversity, and shifted beta diversity toward healthy controls. SEAE-treated fish showed microbial profiles closer to normal than those treated with Metformin. Conclusions SEAE exhibits strong anti-obesity and anti-hyperglycemic effects by modulating key metabolic pathways and restoring gut microbial homeostasis. These findings highlight SEAE as a promising marine-derived therapeutic candidate for metabolic syndrome and warrant further investigation as a functional food or nutraceutical. Clinical trial Not applicable.